Comparison of impact forces, accelerations and ankle range of motion in surfing-related landing tasks - Lundgren, L. E.; Tran, T. T.; Nimphius, S.; Raymond, E.; Secomb, J. L.; Farley, O. R. L.; Newton, R. U.; Sheppard, J. M. (Journal of Sports Sciences, 2016)
This study aimed to describe the impact forces, accelerations and ankle range of motion in five different landing tasks that are used in training and testing for competitive surfing athletes, to assist coaches in the prescription of landing task progression and monitoring training load. Eleven competitive surfing athletes aged 24 ± 7 years participated, and inertial motion sensors were fixed to the anterior aspect of the feet, mid-tibial shafts, sacrum and eighth thoracic vertebrae on these athletes. Three tasks were performed landing on force plates and two tasks in a modified gymnastics set-up used for land-based aerial training. Peak landing force, resultant peak acceleration and front and rear side ankle dorsiflexion ranges of motion during landing were determined. The peak acceleration was approximately 50% higher when performing aerial training using a mini-trampoline and landing on a soft-density foam board, compared to a similar landing off a 50 cm box. Furthermore, the ankle ranges of motion during the gymnastic type landings were significantly lower than the other landing types (P = 0.05 and P = 0.001), for front and rear sides, respectively. Conclusively, increased task complexity and specificity of the sport increased the tibial peak acceleration, indicating greater training load.